Thygeson Superficial Punctate Keratitis: A Clinical and Immunologic Review. Issue 6 (15th June 2022) - Moshirfar, Majid; Peterson, Telyn; Ungricht, Emilie; McCabe, Shannon; Ronquillo, Yasmyne C.; Brooks, Ben; Towne, Francina; Hoopes, Phillip
Abstract: Thygeson superficial punctate keratitis (TSPK) is clinically characterized by exacerbations and remissions of gray–white opacities within the corneal epithelium, most often bilateral but may be asymmetric. Symptoms typically include photophobia, tearing, blurring, and eye irritation. Although disease progression and prognosis are well described, the exact cause is unknown. Hypotheses exist implicating virus-mediated immunity as the cause of TSPK following cases of viral keratitis; however, several polymerase chain reaction studies refute the infectious process concurrently with symptomatic TSPK. This is further supported by the consistent lack of response to antiviral and antibacterial treatment. A subset of dendritic cells known as Langerhans cells (LC) found within the corneal epithelium has been positively correlated with exacerbations of TSPK. Langerhans cells proliferate to protect and mitigate the cornea's inflammatory response, but the inflammatory triggers and relapses associated with TSPK are not well understood. Several topical drugs exist to treat inflammation related to TSPK; however, drug delivery is a major barrier to treatment because of the tear film and epithelial barrier. Drug-eluting contact lenses that target intermediates of inflammation could serve as a more effective treatment modality because of the increased bioavailability of the drugs. This review is an in-depth survey of the literature regarding the relationship between the origin and pathophysiology of LC and TSPK at the immunologic level. We also discuss potential pharmacotherapeutic interventions for TSPK prevention and treatment.